Beneficial Microorganisms Affect Soil Microbiological Activity and Corn Yield under Deficit Irrigation - Josinaldo Lopes Araujo; Jackson de Mesquita Alves; Railene Hérica Carlos Rocha; José Zilton Lopes Santos; Rodolfo dos Santos Barbosa; Francisco Marcelo Nascimento da Costa; Geovani Soares de Lima; Leandro Nunes de Freitas; Adriana Silva Lima; Antonio Elizeneudo Peixoto Nogueira; André Alisson Rodrigues da Silva; Leônidas Canuto dos Santos; et al. (Agriculture, 2023)
Water scarcity is one of the main factors that decrease the growth and productivity of corn, since it negatively affects gas exchange and the general metabolism of the crop. The use of beneficial microorganisms (BM) has been considered a potential attenuator of water stress. This study aimed to evaluate the effect of BM and water deficit on growth, gas exchange, grain yield, and soil microbial activity. A field experiment was carried out, in which the treatments were composed of a 2 × 4 factorial scheme, corresponding to two irrigation levels (100% of ETc and 50% of ETc) and to four treatments (T) referring to the soil inoculation with BM (C: control; T1: Bacillus amyloliquefaciens + Azospirillum brasiliense; T2: B. subtilis; and T3: A. brasiliense). The evaluations were carried out in the flowering phase (plant growth, gas exchange, and foliar nitrogen content) and at the end of the plant cycle (grains yield, mineral nitrogen, and microbiological activity). The 50% reduction in irrigation depth severely restricted corn growth and gas exchange and decreased the grain yield by 38%. The water deficit increased the protein content in the grains and the concentration of mineral nitrogen in the soil when the plants were inoculated with BM. Under water stress, inoculation with BM increased corn productivity by 35% and increased soil microbial activity. The inoculation of plants with BM, either in combination (Bacillus amyloliquefaciens + A. brasiliense) or alone (B. subtilis), attenuated the adverse effects of water deficit in maize.